Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1097/wnf.0000000000000552
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness of Cladribine in Multiple Sclerosis: Real-World Clinical Experience From 5 Tertiary Hospitals in Portugal

Abstract: Objectives: Cladribine is a selective and oral immunological reconstitution treatment, approved in Europe for very active multiple sclerosis (MS) with relapses. Aims were to assess the safety and effectiveness of cladribine in real-world setting, during treatment follow-up.Methods: This was a multicentric, longitudinal, observational study with retrospective and prospective data collection of clinical, laboratory, and imaging data. This interim analysis reports data from July 1, 2018 (study onset), to March 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…On the contrary, real-world observational data of MS cohorts are more representative of routine clinical practice and provide valuable insight into long-term effectiveness and safety [ 74 ]. Several observational real-world cohort studies have assessed the efficacy of cladribine tablets in patients with relapsing forms of MS (RMS) using clinical and MRI assessments [ 44 46 , 75 77 ].…”
Section: Efficacy Of Cladribine Tablets In the Real-world Settingmentioning
confidence: 99%
“…On the contrary, real-world observational data of MS cohorts are more representative of routine clinical practice and provide valuable insight into long-term effectiveness and safety [ 74 ]. Several observational real-world cohort studies have assessed the efficacy of cladribine tablets in patients with relapsing forms of MS (RMS) using clinical and MRI assessments [ 44 46 , 75 77 ].…”
Section: Efficacy Of Cladribine Tablets In the Real-world Settingmentioning
confidence: 99%
“…In the CLARITY study, 14% of patients demonstrated MS disease activity after the first course of CladT, but 61% of these patients demonstrated no further MS disease activity in year 2, following the second course. Real-world evidence suggests that most patients who report MS disease activity during year 1 of treatment do not switch to an alternative DMT, a systematic review of real-world studies with CladT in 3628 people with MS [ 20 ] showed that only 2.4% of patients discontinued or switched away from CladT in the 1st year of treatment (Table 1 ) [ 14 , 65 – 76 ]. The phenomenon of MS disease reactivation after withdrawing an S1P inhibitor or natalizumab is a different phenomenon to residual MS disease activity during the time needed for the efficacy of CladT to build.…”
Section: Patient Management After Initiation Of Cladribine Tabletsmentioning
confidence: 99%
“…of patients No. of discontinuations or switches [N (%)] [ 65 ] Canada 111 0 [ 66 ] Italy 60 1 (1.7) [ 67 ] Spain 85 5 (5.9) [ 68 ] Spain 88 2 (2.3) [ 69 ] Czechia 436 12 (2.8) [ 70 ] USA 616 6 (1.0) [ 71 ] Germany 270 3 (1.1) [ 72 ] Sweden 140 5 (3.5) [ 73 ] United Arab Emirates 88 1 (1.1) [ 14 ] Finland 179 4 (3) [ 74 ] International 610 1 (0.2) [ 75 ] International a 782 31 (4.0) [ 76 ] …”
Section: Patient Management After Initiation Of Cladribine Tabletsmentioning
confidence: 99%
See 1 more Smart Citation